NSF's Experimental Program to Stimulate Competitive Research (EPSCoR): Subsidizing Academic Research or State Budgets? - Wu, Yonghong (Journal of Policy Analysis & Management)
This cross-state empirical study focuses on the National Science Foundation's (NSF) Experimental Program to Stimulate Competitive Research (EPSCoR) and examines its impact on the academic research and development (R&D) expenditures financed by state governments. Based on a panel of 50 states during 1979-2006, the empirical results indicate that EPSCoR, while increasing federal R&D support to EPSCoR states, crowded out financial support for academic research from the governments of EPSCoR states. About one-third of EPSCoR funds went to subsidize state budgets. The crowd-out effect calls for some reconsideration of EPSCoR program design in order to maintain or even increase the state government financial support for academic research activities deemed critical to academic competitiveness and economic prospects. Reprinted by permission of the publisher.